Vinblastine resets tumor-associated macrophages toward M1 phenotype and promotes antitumor immune response - Jing Wang; Jin Wang; Yi-Na Wang; Yuan-Yuan Wang; Wen-Juan Bai; Nai-Jun Miao (Journal for ImmunoTherapy of Cancer)
Background Massive tumor-associated macrophage (TAM) infiltration is observed in many tumors, which usually display the immune-suppressive M2-like phenotype but can also be converted to an M1-like antitumor phenotype due to their high degree of plasticity. The macrophage polarization state is associated with changes in cell shape, macrophage morphology is associated with activation status. M1 macrophages appeared large and rounded, while M2 macrophages were stretched and elongated cells. Manipulating cell morphology has been shown to affect the polarization state of macrophages. The shape of the cell is largely dependent on cytoskeletal proteins, especially, microtubules. As a microtubule-targetting drug, vinblastine (VBL) has been used in chemotherapy. However, no study to date has explored the effect of VBL on TAM shape changes and its role in tumor immune response.Method We used fluorescent staining of the cytoskeleton and quantitative analysis to reveal the morphological differences between M0, M1, M2, TAM and VBL-treated TAM. Flow cytometry was used to confirm the polarization states of these macrophages using a cell surface marker-based classification. In vivo antibody depletion experiments in tumor mouse models were performed to test whether macrophages and CD8+ T cell populations were required for the antitumor effect of VBL. VBL and anti-PD-1 combination therapy was then investigated in comparison with monotherapy. RNA-seq of TAM of treated and untreated with VBL was performed to explore the changes in pathway activities. siRNA mediated knockdown experiments were performed to verify the target pathway that was affected by VBL treatment.Results Here, we showed that VBL, an antineoplastic agent that destabilizes microtubule, drove macrophage polarization into the M1-like phenotype both in vitro and in tumor models. The antitumor effect of VBL was attenuated in the absence of macrophages or CD8+ T cells. Mechanistically, VBL induces the activation of NF-κB and Cyba-dependent reactive oxygen species generation, thus polarizing TAMs to the M1 phenotype. In parallel, VBL promotes the nuclear translocation of transcription factor EB, inducing lysosome biogenesis and a dramatic increase in phagocytic activity in macrophages.Conclusions This study explored whether manipulating cellular morphology affects macrophage polarization and consequently induces an antitumor response. Our data reveal a previously unrecognized antitumor mechanism of VBL and suggest a drug repurposing strategy combining VBL with immune checkpoint inhibitors to improve malignant tumor immunotherapy.